Human Mast Cells (HMC-1 5C6) Enhance Interleukin-6 Production by Quiescent and Lipopolysaccharide-Stimulated Human Coronary Artery Endothelial Cells - Damandeep S. Walia; Mukut Sharma; Vineesh V. Raveendran; Jianping Zhou; Ram Sharma; Daniel J. Stechschulte; Kottarappat N. Dileepan (Mediators of Inflammation)
We examined the effect of intact human mast cells (HMC-1 5C6) and their selected mediators on interleukin-6 (IL-6) production and bone morphogenetic protein-2 (BMP-2) expression in human coronary artery endothelial cells (HCAEC) in the presence and absence of lipopolysaccharide (LPS). Scanning electron microscopy showed that HMC-1 5C6 cells adhere to HCAEC in cocultures. Addition of HMC-1 5C6 cells markedly enhanced the IL-6 production by quiescent and LPS-activated HCAEC even at the maximal concentration of LPS. Furthermore, mast cell-derived histamine and proteases accounted for the direct and synergistic effect of mast cells on IL-6 production that was completely blocked by the combination of histamine receptor-1 antagonist and protease inhibitors. Another novel finding is that histamine was able to induce BMP-2 expression in HCAEC. Collectively, our results suggest that endotoxin and mast cell products synergistically amplify vascular inflammation and that histamine participates in the early events of vascular calcification.